Metastatic Renal Cell Carcinoma to Jejunum: An Unusual Case Presentation - Medic, Igor (Urol Case Rep, 2017)
The small intestine is a very uncommon and peculiar site for metastasis from renal cell carcinoma (RCC). We present a clinical presentation of insidious and unusual development of a jejunal metastasis while having stable disease in a remainder of metastatic sites, in a patient undergoing immunotherapy with nivolumab. Due to the extreme rarity of metastatic renal cell carcinoma to the lumen of the small bowel, it is easy to overlook and misdiagnose symptoms of this pathologic entity, particularly when the remainder of metastatic disease responds well to ongoing therapy.